Efektivitas Penggunaan Media Trainer pada Mata Pelajaran Instalasi Motor Listrik - Dahlia Dahlia; Taali Taali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study aims to determine the effectiveness of the use of trainer media on student learning outcomes in the subject of Electric Motor Installation at SMK Negeri 5 Padang. The low learning outcomes of students and difficulties in answering questions about practical material during the exam are caused by the lack of enthusiasm and independence of students during the learning process of Electrical Motor Installation, thus affecting the cognitive and psychomotor domains of students. Therefore, it is necessary to conduct research with the use of trainer media to see the effectiveness of student learning outcomes. This research uses a type of experimental research that is categorized into a type of pre-experiment research design with a one-group pretest post-test design. The subject of this research is class XI TITL 1 SMK Negeri 5 Padang in the 2022/2023 school year consisting of 35 students. To measure the effectiveness of this study, a pretest was given before the use of trainer media in learning. The post-test was given after the learning process using the trainer media in the learning process of the Electric Motor Installation practice. And on skill assessment using skill assessment sheets consisting of 5 aspects of assessment. The results of the study were analyzed using class completeness testing, effect size, and skills assessment. The test results show that the value of students who applied using trainer media is better than before using trainer media. The learning outcomes of students after using the media trainer increased, so the use of media trainers is effective for improving student learning outcomes.